P335 Impact of cancer therapy on the course of Inflammatory Bowel Disease (ONCOEII study of GETECCU). (30th January 2023) - Pérez Galindo, P; Benítez, J M; Rubín de Célix, C; Mesonero, F; Castaño García, A; García, M J; Vicuña, M; Bernal, L; Bertoletti, F; Ramírez Castro, C; Sánchez-Azofra, M; Sánchez-Delgado, L; et al.
Abstract: Background: Cancer in inflammatory bowel disease (IBD) patients is increasing mainly due to the aging of patients. There are few data regarding the effect of different types of cancer treatments in IBD disease outcome. The aim of the study was to evaluate the impact of cancer treatments on the course of IBD patients. Methods: An observational, multicenter, retrospective cohort study was conducted. We identified IBD patients diagnosed for an extraintestinal malignancy and who received any of the following cancer treatment types: chemotherapy, hormonal therapy, targeted therapy or immunotherapy. Patients who simultaneously received more than one different type of cancer treatment were excluded. Primary outcome was to evaluate the risk of IBD relapse for each type of cancer treatment. IBD relapse was defined as the need for additional medication, hospitalization or surgery related to IBD. Secondary outcomes were to describe the IBD treatment modifications after cancer diagnosis and to identify predictive factors for IBD relapse. IBD relapse was defined as the need for additional medication, hospitalization or surgery related to IBD. Predictive factors for IBD relapse were identified using multivariate Cox proportional hazard analysis. Results: A total of 180 patients from 26 centers were included. Median age at cancer diagnosis was 57.5 years (IQR 46.8-67), 52.2% were female and 51.1% had Crohn's disease. 36.1% and 20.6% were receiving immunomodulators and biologic drugs at the moment of cancer diagnosis respectively. IBD was in remission in most of the patients (85%). The most frequent malignancies were breast, prostate and hematological (33.9%, 12.2% and 12.2% respectively). IBD treatment was discontinued in 40.6% of patients at cancer diagnosis (77.1% of patients receiving thiopurines and 79.2% of those receiving anti-TNF drugs). 33% of patients experienced IBD relapse after cancer treatment initiation, at a median time of 7.6 months. IBD relapse was treated more frequently with steroids, vedolizumab and anti-TNF (56%, 15.2% and 13.6% respectively). In multivariate Cox-regression analysis, older age (HR=0.98; 95% CI [0.96-0.99]) and chemotherapy (HR=0.57; 95% CI [0.34-0.96]) were associated with a lower risk of IBD relapse, and active IBD at baseline (HR=2.9; 95% CI [1.67-5.07] was associated with a higher risk. Kaplan-Meier survival curves for time to IBD relapse are shown in Figures 1 and 2. Conclusion: One out of three patients experienced IBD relapse after cancer treatment initiation. IBD drugs were discontinued in almost half of the cohort, specially thiopurines and anti-TNF drugs. Older age and chemotherapy were associated with a lower risk of IBD relapse, and active IBD at baseline with a higher risk.